KAJIAN DAMPAK IMPLEMENTASI KEBIJAKAN REDENOMINASI RUPIAH - Nur Alam (JURNAL KEBIJAKAN PUBLIK, 2018)
This article is the brainchild of the government's policy plan that will do the rupiah redenomination. As we ketahu that the core of the currency redenomination is a simplification of the digits disappear rupiah. The study in this article analyzes the impact of more negative and positive when the rupiah redenomination policy actually done by the government. History, concepts and economic analysis both micro and macro equipped in this article. some case studies on the impact on the economy in Indonesia to be part of exciting to be associated with the redenomination policy. The final conclusion of this article suggests that if done then the rupiah redenomination policy needs to be studied more in depth about the impact on society, and not just the mere pursuit of prestige. Thoroughly and gradual socialization is an important recommendation in this article.